2016
DOI: 10.5306/wjco.v7.i4.324
|View full text |Cite
|
Sign up to set email alerts
|

Risk of second primary malignancies in a population-based study of adult patients with essential thrombocythemia

Abstract: AIM:To determine the risk of second primary malignancy (SPM) and survival of patients with essential thrombocythemia (ET). METHODS:We identified all patients with ET diagnosed during 2001 to 2011 from the Surveillance, Epidemiology and End Results (SEER) 18 database. Actuarial and relative survival methods were used to calculate the survival statistics. We utilized the SEER 13 database to calculate SPM. We used multiple primary standardized incidence ratio (SIR) session of the SEER*Stat software (version 8.1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
1
6
1
Order By: Relevance
“…For example, in the study by Chattopadhyay et al, the relative increase in second cancer risk was highest in MPN patients aged ≤ 65 years, with IRRs ranging from 1.7- to 3.7-fold elevated in patients with ET, PV, MF and MPN-U, whereas the IRRs ranged from 1.3- to 1.8-fold elevated in patients aged > 65 years [ 13 ]. The same tendency was seen in other studies, with SIRs for second cancer of 1.8 for PV patients aged ≤ 60 years and 1.2 in patients aged > 60 years [ 23 ]; or ET patients with SIRs of 1.8 and 1.2 for ages ≤ 60 years and > 60 years, respectively [ 28 ]. In the study by Landtblom et al, the overall cumulative incidence of cancer increased with increasing age for both patients and matched comparisons [ 11 ].…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…For example, in the study by Chattopadhyay et al, the relative increase in second cancer risk was highest in MPN patients aged ≤ 65 years, with IRRs ranging from 1.7- to 3.7-fold elevated in patients with ET, PV, MF and MPN-U, whereas the IRRs ranged from 1.3- to 1.8-fold elevated in patients aged > 65 years [ 13 ]. The same tendency was seen in other studies, with SIRs for second cancer of 1.8 for PV patients aged ≤ 60 years and 1.2 in patients aged > 60 years [ 23 ]; or ET patients with SIRs of 1.8 and 1.2 for ages ≤ 60 years and > 60 years, respectively [ 28 ]. In the study by Landtblom et al, the overall cumulative incidence of cancer increased with increasing age for both patients and matched comparisons [ 11 ].…”
Section: Resultssupporting
confidence: 84%
“…We found that for patients with ET, SIRs for cancer incidence diminished during the first 5 years following diagnosis, whereas the opposite was seen in patients with PV and CML [ 10 ]. Shresta and colleagues reported on insignificant increases in SIR for solid cancer two years after ET diagnosis [ 28 ]. Landtblom et al showed that HRs for any solid cancer and for non-melanoma skin cancer decreased steeply during the first year and gradually increased thereafter [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Registry studies from Europe and US consistently reported non‐MPN cancers in about 17% of patients with MPN: a 20%‐40% higher risk of non‐MPN cancers was reported in the years preceding and following the diagnosis of MPN . In particular, the standardized risk of non‐Hodgkin's lymphomas was reported to be 1.8 (1.1–2.7) in the Danish registry, 4.52 (2.26‐0.09) in the Florence database, 1.1 (0.55‐1.88), and 1.59 (0.82‐2.78) for PV and ET, respectively, in the SEER database . Nevertheless, the above four studies could analyze only 56 overall patients with both MPN and LPD.…”
Section: Discussionmentioning
confidence: 97%